1977
DOI: 10.1037/0021-9010.62.3.335
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the influence of job level and functional specialty on job attitudes and perceptions.

Abstract: One hundred and fifty-two jobs in a large (N = 1,313) midwestern printing company were classified into vertical (job level) and horizontal (functional specialty) distributions to investigate differences in employee attitudes. Descriptions of leader behavior (the Leader Behavior Description Questionnaire's Initiating Structure scale) and four aspects of satisfaction (the Job Descriptive Index Scales: Satisfaction with Work, Pay, Supervision, and Co-Workers) were assessed. A 3 (job level) X 5 (functional special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

1979
1979
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 13 publications
1
19
0
2
Order By: Relevance
“…Evidence on the impact of functional specialty, job level, and employee demographics also has indicated that functional specialty and level are of greater importance in explaining employee responses than employee demographics or individual traits (Adams, Laker, & Hulin, 1977;Fry & Greenfield, 1980;Herman, Dunham, & Hulin, 1975;Herman & Hulin, 1972;Hulin, Hom, & Brett, 1976;O'Reilly & Roberts, 1975;Roznowski & Hulin, 1985). Whatever personal demographics may be indexing is less important in accounting for attitudes toward and about life in organizations than is the position one occupies within the organization.…”
Section: Gender Advantage and Transformational Leadershipmentioning
confidence: 92%
“…Evidence on the impact of functional specialty, job level, and employee demographics also has indicated that functional specialty and level are of greater importance in explaining employee responses than employee demographics or individual traits (Adams, Laker, & Hulin, 1977;Fry & Greenfield, 1980;Herman, Dunham, & Hulin, 1975;Herman & Hulin, 1972;Hulin, Hom, & Brett, 1976;O'Reilly & Roberts, 1975;Roznowski & Hulin, 1985). Whatever personal demographics may be indexing is less important in accounting for attitudes toward and about life in organizations than is the position one occupies within the organization.…”
Section: Gender Advantage and Transformational Leadershipmentioning
confidence: 92%
“…Many edrly studies using the JUI as a multivariate instrument have provided evidence that the five scales are not redundant when treated as five separate dimensions in empirical research: each provides some important, scientifically meaningful unique variance (Adams, Laker, and Hulin, 1977;Herman, Dunham, and Hulin, 1975). It is nevertheless true that the general Translating the JDI also seems to be an example where the unidimensionality assumption is useful and does not do gross violence to the data.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the dispersion of satisfaction at various levels of the psychiatric hospital hierarchy is not healthy. For example, it has been well documented across successful companies in various industries that job satisfaction increases as job level increases (Adams, Laker, & Hulin, 1977;Porter & Lawler, 1965;Robie, Ryan, Schmieder, Parra, & Smith, 1998;Smith & Brannick, 1990). This same pattern has also been found in medical and surgical hospitals (Robie et al, 1998), yet no studies have examined this issue in private psychiatric hospitals.…”
mentioning
confidence: 79%